La ‘scuola’ italiana di scienza delle finanze.(The Italian ‘school’ of public economics) - Giuseppe Dallera (Moneta e Credito, 2013)
The article summarises the evolution of the Italian school of public finance, highlighting those themes that most attracted James Buchanan's interest. It considers such topics as the operations of the fiscal authorities, the Leviatan monopolist, financial delusion, public debt theory, and the theory of taxation.